EDUKASI PENGGUNAAN BAHAN TAMBAHAN PANGAN (BTP) YANG AMAN UNTUK MENINGKATKAN LITERASI KEAMANAN PANGAN PADA ANGGOTA PNM (PERMODALAN NASIONAL MADANI) - Hurip Budi Riyanti; Adia Putra Wirman; Euis Purbasari; Oktadio Erikardo; Nurul Azmah Nikmatullah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Improper use of food additives and the misuse of hazardous non-food substances such as borax, formaldehyde, rhodamine B, and metanil yellow remain food-safety problems in the community. Low literacy regarding permitted additives, their maximum limits, and label reading increases the risk of exposure. This community-service activity aimed to improve the knowledge of members of PMN (Permodalan Mekar Madani) on the safe use of food additives and the recognition of prohibited hazardous substances. The activity was held at the Faculty of Pharmacy and Science, UHAMKA, Jakarta, on 5 May 2026 with 20 participants, comprising interactive counselling, recognition of product characteristics, and application of the Cek KLIK approach, and was evaluated through a pre-test and post-test. The results showed an increase in the mean knowledge score from 55 to 85, a gain of 30 points (54.55%). This activity concludes that structured education effectively improves partners' food-safety literacy.